Earthquake disaster resilience in Taiwan observed from the April 2024 ML 7.1 Hualien earthquake - Enokida, Ryuta; Fukushima, Yo; Tang, Chi-Hsien; Pan, Tsung-Yi; Kuo, Chun-Lin; Ikago, Kohju; Izumi, Takako; Kuriyama, Shinichi (Frontiers in Built Environment, 2025)
This study investigated Taiwan’s earthquake disaster resilience and remaining challenges after the Hualien earthquake, which occurred at 07:58 a.m. local time (UTC+8) on 3 April 2024. Through a survey, we found possible factors for the relatively suppressed damage caused by this earthquake. The 2024 Hualien earthquake (ML: 7.1) was not as severe as the 2018 earthquake (ML: 6.2) in terms of the maximum velocity of ground motion, which greatly affected the structural damage, owing to the different mechanisms of the earthquakes. Earthquake-resistant measures in Taiwan have high standards, such as building codes and seismic monitoring networks. At the 2024 earthquake, early warning systems and data-sharing networks for seismic records were useful for prompting immediate evacuation. Based on rapidly shared information and predesigned frameworks, disaster response operations quickly made evacuations, rescues, and other decisions. In addition to these government actions, support from non-government organizations (NGOs) has greatly contributed to evacuation, shelter management, and evacuee care in severely affected areas. The timing of this earthquake positively acted to limit the impact on Taroko National Park, as it was not the peak time for visitors, although the park still had the majority of casualties caused by landslides. These lessons can be possibly reflected in earthquake disaster resilience in other countries.